(untitled) (Community Based Medical Journal, 2021)
Although both mycobacterial infections are endemic in developing countries, the coinfection has hardly been reported in the last decade. The combined National TB & Leprosy Control Programme of Bangladesh came into effect in 1994. Though the Elimination of Leprosy (<1 case / 10,000 population) was achieved nationally in 1998, Bangladesh is still endemic for Tuberculosis. A 10 years cohort study was conducted in six districts of the Northern part of Bangladesh, covered by the Damien Foundation. This cohort consisted of a total of 4,788 leprosy cases registered from 2007 to 2016. Reviewing the records of all these cases, 25 (0.52%) patients were identified as having coinfection with Tuberculosis & Leprosy. All cases were coinfected with smear positive pulmonary TB. This study concludes that duel infection with mycobacteria is uncommon. Early diagnosis is very important for better outcomes of both diseases. CBMJ 2020 July: Vol. 09 No. 02 P: 39-41